Integrated Population Administration System With Automated WhatsApp Notifications: Sistem Administrasi Kependudukan Terpadu dengan Notifikasi WhatsApp Otomatis - Erma Puspita; Nuril Lutvi Azizah; Cindy Taurusta; Yunianita Rahmawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Digital transformation has become essential for improving the quality and responsiveness of public administrative services, particularly those managing large volumes of citizen data. Specific Background: Population administration services at the sub-district level in Kecamatan Waru have faced challenges related to manual data processing, limited service transparency, and the lack of direct notification mechanisms for informing applicants about document progress. Knowledge Gap: Existing studies tend to address population data management systems or notification features separately, while integrated implementation combining administrative systems with automated messaging services at the sub-district level remains limited. Aims: This study aimed to design and implement a web-based population administration information system integrated with the WhatsApp Business API using the Rapid Application Development method. Results: The developed system enables centralized management of population service data and automatically sends document status notifications to applicants through WhatsApp; functional testing confirmed system reliability, and user acceptance testing recorded a satisfaction score of 91.43%. Novelty: The study offers an applied model of integrating population administration services with automated WhatsApp notifications that has been implemented and evaluated in an actual sub-district setting. Implications: This system supports more transparent, timely, and user-oriented public services by reducing information delays and improving communication between government offices and citizens. Highlights: Centralized Web Management Streamlined Handling of Citizen Service Applications. Automated Messaging Delivered Timely Document Status Updates to Applicants. User Evaluation Indicated High Acceptance Among Sub-District Service Staff. Keywords: Population Administration, Information System, Rapid Application Development, Whatsapp Blast, Public Service